JEJAK-JEJAK BUDAYA PENUTUR AUSTRONESIA DI SUMATERA SELATAN - Harry Octavianus Sofian (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Austronesian language speakers migrated to Southeast Asia and Indo-Pacific around 3500 years ago. Austronesian language speakers left traces of technology and cultures through the remains of artefacts. No exception in the area of South Sumatra also indicates the presence of the artefacts and cultures that characterize the Austronesian language speaking cultures. This paper will discuss the trail Austonesia speakers in South Sumatra through the remains of its culture.